(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To develop a mobile application for wound analysis that includes the TIMERS framework, a human body map, and wound assessment criteria for nursing professionals and students. Method: This study employed a methodological research approach focused on technological development. The research was conducted in three stages: the pre-project phase, the structuring of the research through a literature review on the topic, and the evaluation phase, which involved developing the prototype. Results: A prototype of the application, Avalia Feridas, was initially created, limited to the Android operating system. This app includes the TIMERS framework, wound assessment criteria, and a human body map. The application aims to enhance nursing care by providing individualized interventions, thereby contributing to the wound healing process. Conclusion: The application supports the development of critical thinking in wound assessment, offering guidance to nursing students and professionals in their practice. The next objective is to validate the app, with the goal of making this tool available to the public. DESCRIPTORS: Technology. Nursing care. Nursing assessment. Enterostomal therapy. Wounds and injuries.